2018
DOI: 10.1016/j.molcel.2018.02.034
|View full text |Cite|
|
Sign up to set email alerts
|

Separating Actin-Dependent Chemokine Receptor Nanoclustering from Dimerization Indicates a Role for Clustering in CXCR4 Signaling and Function

Abstract: A current challenge in cell motility studies is to understand the molecular and physical mechanisms that govern chemokine receptor nanoscale organization at the cell membrane, and their influence on cell response. Using single-particle tracking and super-resolution microscopy, we found that the chemokine receptor CXCR4 forms basal nanoclusters in resting T cells, whose extent, dynamics, and signaling strength are modulated by the orchestrated action of the actin cytoskeleton, the co-receptor CD4, and its ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 73 publications
11
102
0
Order By: Relevance
“…CXCR4 is a 352 amino acid rhodopsin-like GPCR, comprising an extracellular N-terminal domain, 7 transmembrane (TM) helices, 3 extra-cellular loops (ECL), 3 intra-cellular loops (ICL) and an intracellular C-terminal domain ( 6 ). CXCR4 can exist in the plasma membrane as a monomer, dimer, higher-order oligomer or nanoclusters ( 7 ), although the partitioning and relevance of these different multimerization states has not been addressed in vivo . Several crystal structures of CXCR4 bound to agonists and small molecules are in accordance with the ability of CXCR4 to form homodimers via interactions of the TM5 and TM6 helices ( 6 ).…”
Section: Cxcr4 and Its Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR4 is a 352 amino acid rhodopsin-like GPCR, comprising an extracellular N-terminal domain, 7 transmembrane (TM) helices, 3 extra-cellular loops (ECL), 3 intra-cellular loops (ICL) and an intracellular C-terminal domain ( 6 ). CXCR4 can exist in the plasma membrane as a monomer, dimer, higher-order oligomer or nanoclusters ( 7 ), although the partitioning and relevance of these different multimerization states has not been addressed in vivo . Several crystal structures of CXCR4 bound to agonists and small molecules are in accordance with the ability of CXCR4 to form homodimers via interactions of the TM5 and TM6 helices ( 6 ).…”
Section: Cxcr4 and Its Ligandsmentioning
confidence: 99%
“…Several crystal structures of CXCR4 bound to agonists and small molecules are in accordance with the ability of CXCR4 to form homodimers via interactions of the TM5 and TM6 helices ( 6 ). TM6 is also implicated in nanoclustering ( 7 ). CXCR4 can also form heterodimers with ACKR3 (a related GCPR also known as CXCR7), which have distinctive signaling properties ( 8 ).…”
Section: Cxcr4 and Its Ligandsmentioning
confidence: 99%
“…The stoichiometry of the different forms could also vary according to cell type and among different patients, possibly contributing to the phenotypic heterogeneity observed in different patients with the same pedigree. Moreover, it has recently been reported that in addition to the ligand-mediated conformational change of the receptor that activates G proteins, CXCR4 undergoes changes associated with receptor nanoclustering that are necessary for signaling and could establish a new target for potential intervention in WHIM and WM patients [81]. A deeper understanding of the functional and pharmacological properties of CXCR4 heterodimers may therefore indicate more specific targets for drug design and development.…”
Section: Effect Of Homo or Heterodimerization On Whim-mutated Cxcr4 Smentioning
confidence: 99%
“…For instance, chemokines are capable of forming dimers and oligomers (1517), and can interact with synergy-inducing molecules (18) and with glycosaminoglycans (GAGs) (17, 19, 20). It is also known that chemokine receptors are not only monomeric entities, but also exist as dimers and higher-order oligomers (21) that also interact with other membrane proteins (2124) and exhibit signaling crosstalk with other proteins (25, 26).…”
Section: Introductionmentioning
confidence: 99%